The Hybrid Identity of Urban Muslim Youth: The Case of Teras Dakwah Yogyakarta - Saputra, Eko; Rosidi, Imron (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2022)
This paper describes the phenomenon of hybrid identity among young urban Muslims in the popular da'wah movement in Yogyakarta. This research uses an ethnographic approach to take a case study of Teras Da'wah. This research argues that today's da'wah movement is oriented towards market Islam or market religion. The consequence of this market Islam is that it gives birth to an unusual da'wah movement, namely the identity of young Muslim hybrids who appreciate various Islamic ideologies. In addition, their hybrid identity also impacts how Teras Da'wah values symbols of popular culture, such as developing an office or da'wah center resembling a modern cafe, using social media, and slang dictions in preaching and using contemporary da'wah themes. It also uses music, films, futsal, and hanging out culture as an instrument of da'wah. This puts da'wah in a form that fits the identity of urban Muslim youths, who are pious and modern.